An assessment of physical development in religious educational in Malaysia: case study of SAR and SABK in Perak - Mohamed Osman, Mariana; Bachok, Syahriah; Ahmad Thani, Siti Nur 'Alia; Ibrahim, Mansor (Elsevier B.V., 2015)
Education, public awareness and training are the keys towards sustainability. Focusing on the Sekolah Agama Rakyat/SMAR (People's Religious School) and Sekolah Agama BantuanKerajaan/SABK (Religious School of Government Assistance), an assessment on school facilities has been done. The research only focused on the physical factors of the SMAR and SABK. Quantitative methods were conducted with 16 schools of SMAR and SABK are involved. Findings indicate that SMAR and SABK generally do not provide adequate facilities to the students for their education. Therefore there is a need for better solutions such as increase in government financial aid, renovation and improvement of school building from government and related agencies.